Negative electrode for lithium secondary battery and method for producing same
By dividing and aligning the carbon-based negative electrode active materials in each region in the negative electrode active layer of the lithium-ion secondary battery, the problems of reducing the N/P ratio and forming the lithium resin are solved, and a battery with high load capacity and excellent fast charging performance is achieved.
Patent Information
- Application Number
- JP2024556535
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-02-09
- Filing Date
- 2023-11-27
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-11-27
AI Technical Summary
During the manufacturing process of existing lithium-ion secondary batteries, the N/P ratio between the positive electrode active layer and the negative electrode active layer is easily reduced, resulting in lithium ions deposited on the negative electrode surface to form lithium resin, increasing battery safety risks and affecting fast charging performance.
By dividing the center area, sliding area and edge area in the negative electrode battery active layer, and applying a magnetic field to oriented the negative electrode battery active layer during the manufacturing process, it is ensured that the alignment of the carbon-based negative electrode active material in each area meets a specific range, so as to improve the load capacity and fast charging performance of the negative electrode active layer.
It effectively inhibits the deposition of lithium ions at the negative electrode end, improves the fast charging performance of lithium ion secondary batteries, and improves the safety of the battery.
Smart Images

Figure 2025511598000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for a lithium secondary battery and a method for producing the same.
[0002] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0183016 dated December 23, 2022 and Korean Patent Application No. 10-2023-0017427 dated February 9, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated herein by reference. [Background technology]
[0003] 2. Description of the Related Art In recent years, secondary batteries have been widely used not only in small devices such as portable electronic devices, but also in medium- to large-sized devices such as battery packs for hybrid and electric vehicles and power storage devices.
[0004] Such secondary batteries are power generating elements capable of being charged and discharged and have a laminated structure of a positive electrode / separator / negative electrode. In general, the positive electrode contains a lithium metal oxide as a positive electrode active material, and the negative electrode contains a carbon-based active material such as graphite. During charging, lithium ions released from the positive electrode are absorbed into the carbon-based active material of the negative electrode, and during discharging, the lithium ions contained in the carbon-based active material are absorbed into the lithium metal oxide of the positive electrode, thereby allowing repeated charging and discharging.
[0005] Meanwhile, one of the factors that influence the performance of a secondary battery is the capacity ratio of the active materials contained in the positive and negative electrodes. The capacity ratio can be expressed as the N / P ratio, which is the total capacity of the negative electrode calculated by considering the capacity per area and / or weight of the negative electrode divided by the total capacity of the positive electrode calculated by considering the capacity per area and / or weight of the positive electrode, and since it has a significant effect on the safety and capacity of the battery, it is generally adjusted to have a value of 1 or more.
[0006] However, in the manufacturing process of a lithium secondary battery, if the positive electrode active layer separates from the negative electrode active layer when the positive and negative electrodes are stacked, an inversion phenomenon occurs in which the N / P ratio becomes smaller than 1. If the N / P ratio becomes smaller than 1, lithium ions cannot be fully intercalated into the negative electrode active material during charging of the battery, and instead precipitate on the surface of the negative electrode to form dendrites. The likelihood of dendrites occurring increases significantly, especially when the lithium secondary battery is used for a long time under high-rate conditions. The dendrites formed in this way can induce an internal short circuit in the battery, and thus act as a factor that impairs the safety of the battery.
[0007] In order to solve this problem, attempts have been made to increase the loading amount of the negative electrode active material at the end of the active layer of the conventional negative electrode, but in this case, there is a limit in that as the loading amount of the negative electrode active material increases, the migration distance of lithium ions in the negative electrode increases, which may degrade the fast charging characteristics, etc., and therefore the commercial viability of the battery may decrease.
[0008] Therefore, there is a strong need for a technology that can maintain or improve fast charging characteristics at a certain level or higher even if the loading amount of the negative electrode active material at the end of the negative electrode active layer increases in order to suppress lithium precipitation at the end of the negative electrode active layer. Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a negative electrode for a lithium secondary battery having a high loading amount of negative electrode active material at the end of the negative electrode active layer and excellent high-speed charging performance in order to suppress lithium precipitation at the end of the negative electrode active layer, and a method for producing the same. [Means for solving the problem]
[0010] To solve the above-mentioned problems, In one embodiment, the present invention comprises: a negative electrode current collector; and a negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a carbon-based negative electrode active material, The negative electrode active layer is The negative electrode active layer is divided into a central region including a center portion in a width direction thereof, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region, Provided is a negative electrode for a lithium secondary battery that satisfies the following formulas 1 and 2:
[0011] [Formula 1] 2.7≦[OI edge ] / [OI center ]≦4.8
[0012] [Formula 2] 1.5≦[OI sliding ] / [OI center ]≦2.6
[0013] (In formula 1 and formula 2, OI edge represents the alignment degree (OI) in the edge region, OI center represents the degree of alignment (OI) in the central region, OI sliding represents the degree of alignment (OI) in the sliding domain, The degree of alignment (OI) is the area (I 004 ) and the area of the peak representing the (1,1,0) crystal plane (I 110 ) percentage (I 004 / I 110 )
[0014] At this time, the central region of the negative electrode active layer has an alignment degree (OI center ) may be 0.7 to 1.5.
[0015] In addition, the central region of the negative electrode active layer may account for 90% or more of the overall length of the negative electrode active layer in the width direction, and the sliding region of the negative electrode active layer may account for 3% or less of the overall length of the negative electrode active layer in the width direction.
[0016] The central region of the negative electrode active layer may have an average thickness of 100 μm to 300 μm, and the sliding region of the negative electrode active layer may have an exposed surface with an inclination angle of 70° or more with respect to the negative electrode current collector.
[0017] Meanwhile, the carbon-based active material may include one or more of natural graphite and artificial graphite.
[0018] Further, in one embodiment, the present invention provides Applying a negative electrode slurry containing a carbon-based active material onto a negative electrode current collector; applying a magnetic field to the applied negative electrode slurry; and drying the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer; The negative electrode active layer is divided into a central region including a center portion in a width direction of the negative electrode active layer, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region, and the negative electrode active layer satisfies the following formulas 1 and 2:
[0019] [Formula 1] 2.7≦[OI edge ] / [OI center ]≦4.8
[0020] [Formula 2] 1.5≦[OI sliding ] / [OI center ]≦2.6
[0021] (In formula 1 and formula 2, OI edge represents the alignment degree (OI) in the edge region, OI center represents the degree of alignment (OI) in the central region, OIsliding represents the degree of alignment (OI) in the sliding domain, The degree of alignment (OI) is the area (I 004 ) and the area of the peak representing the (1,1,0) crystal plane (I 110 ) percentage (I 004 / I 110 )
[0022] Here, in the step of applying the negative electrode slurry, the applied negative electrode slurry may satisfy the following formula 3:
[0023] [Formula 3] R sliding <R center <R edge
[0024] (In formula 3, R sliding represents the average thickness of the sliding region, R edge represents the average thickness of the edge region, R center represents the average thickness of the central region)
[0025] In addition, in the step of applying the magnetic field, a magnetic field of 2,000 G to 6,000 G may be applied, and the application time may be 5 seconds to 60 seconds.
[0026] In addition, the step of applying the magnetic field is performed by magnet parts introduced above and below the applied negative electrode slurry, and the magnet parts may have a length of 105% to 200% based on the width direction length of the negative electrode slurry.
[0027] In addition, the step of forming the negative electrode active layer may include the steps of drying the negative electrode slurry and rolling the dried negative electrode slurry.
[0028] At this time, the edge region of the negative electrode active layer may have a thickness ratio of 105% to 130% based on the average thickness of the central region of the negative electrode active layer before rolling. Effect of the Invention
[0029] The negative electrode for a lithium secondary battery according to the present invention includes a negative electrode active layer on a negative electrode current collector, the negative electrode active layer being divided into a central region, an edge region, and a sliding region, and the degree of alignment (OI) of each carbon-based negative electrode active material contained in the central region, the edge region, and the sliding region satisfies Equation 1 and Equation 2, thereby suppressing lithium deposition at the edge of the negative electrode active layer, and a secondary battery including the same has an advantage of excellent high-speed charging performance. [Brief description of the drawings]
[0030] [Figure 1] 1 is an image showing a cross-sectional structure of a negative electrode according to the present invention. [Diagram 2] 1 is an image showing a cross-sectional structure of a negative electrode according to the present invention. [Diagram 3] 4 is an image showing a cross-sectional structure of a negative electrode active layer that is not rolled after drying of a negative electrode slurry in manufacturing a negative electrode according to the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] Since the present invention can be modified in various ways and can have various embodiments, a specific embodiment will be described in detail.
[0032] However, this is not intended to limit the invention to any particular embodiment, but it should be understood to include all modifications, equivalents, or alternatives falling within the spirit and scope of the invention.
[0033] In the present invention, terms such as "comprise" and "have" are intended to specify the presence of features, numbers, steps, operations, components, parts, or combinations thereof described in the specification, and may be understood as not precluding the presence or additional possibility of one or more other features, numbers, steps, operations, components, parts, or combinations thereof.
[0034] In addition, in the present invention, when a layer, film, region, plate, or other portion is described as being "on" another portion, this includes not only the case where it is "directly on" the other portion, but also the case where there is another portion in between. Conversely, when a layer, film, region, plate, or other portion is described as being "under" the other portion, this includes not only the case where it is "directly under" the other portion, but also the case where there is another portion in between. In addition, in the present application, being "on" can include not only the case where it is located at the top, but also the case where it is located at the bottom.
[0035] In the present invention, "containing as a main component" may mean containing 50% by weight or more (or 50% by volume or more), 60% by weight or more (or 60% by volume or more), 70% by weight or more (or 70% by volume or more), 80% by weight or more (or 80% by volume or more), 90% by weight or more (or 90% by volume or more), or 95% by weight or more (or 95% by volume or more) of a defined component based on the total weight (or total volume). For example, "containing graphite as a main component as a negative electrode active material" may mean containing 50% by weight or more, 60% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, or 95% by weight or more of graphite based on the total weight of the negative electrode active material, and in some cases, it may mean that the entire negative electrode active material is made of graphite and contains 100% by weight of graphite.
[0036] In addition, in this specification, "the carbon-based negative electrode active material is oriented" or "the carbon-based negative electrode active material is aligned" means that the crystal planes of the carbon-based negative electrode active material constituting the negative electrode active material particles are distributed to have a predetermined directionality based on the surface of the negative electrode current collector, which may be different from the particles of the carbon-based negative electrode active material being arranged to have a specific direction inside the negative electrode active layer.
[0037] In addition, "high orientation of the carbon-based negative electrode active material" may mean that the carbon-based negative electrode active material contained in the negative electrode active layer is aligned with high frequency with respect to the surface of the negative electrode current collector, and in some cases, may mean that the carbon-based negative electrode active material contained in the negative electrode active layer is aligned at a high angle with respect to the surface of the negative electrode current collector.
[0038] In addition, "high degree of alignment of the carbon-based negative active material" may mean that the "degree of alignment (OI)" referred to in this specification is large, and the carbon-based negative active material contained in the negative active layer is aligned at a low angle based on the surface of the negative current collector. Conversely, "low degree of alignment of the carbon-based negative active material" may mean that the "degree of alignment (OI)" is small, and the carbon-based negative active material contained in the negative active layer is aligned at a high angle based on the surface of the negative current collector.
[0039] The present invention will now be described in more detail.
[0040] <Negative electrodes for lithium secondary batteries>
[0041] In one embodiment, the present invention comprises: a negative electrode current collector; and a negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a carbon-based negative electrode active material, The negative electrode active layer is The negative electrode active layer is divided into a central region including a center portion in a width direction of the negative electrode active layer, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region, Provided is a negative electrode for a lithium secondary battery that satisfies the following formulas 1 and 2:
[0042] [Formula 1] 2.7≦[OI edge ] / [OI center ]≦4.8
[0043] [Formula 2] 1.5≦[OI sliding ] / [OI center ]≦2.6
[0044] (In formula 1 and formula 2, OI edge represents the alignment degree (OI) in the edge region, OI center represents the degree of alignment (OI) in the central region, OIsliding represents the degree of alignment (OI) in the sliding domain, The degree of alignment (OI) is the area (I 004 ) and the area of the peak representing the (1,1,0) crystal plane (I 110 ) percentage (I 004 / I 110 )
[0045] 1 and 2 are cross-sectional views showing the structures of negative electrodes 100 and 200 according to the present invention, in which a negative electrode active layer is provided on one surface of a negative electrode current collector.
[0046] The negative electrodes 100 and 200 for lithium secondary batteries according to the present invention include negative electrode active layers 120 and 220 including a carbon-based negative electrode active material on at least one surface of the negative electrode current collectors 110 and 210. The negative electrode active layers 120 and 220 are layers that realize the electrical activity of the negative electrode. The negative electrode active layers 120 and 220 are manufactured by applying a negative electrode slurry including a negative electrode active material that realizes an electrochemical oxidation-reduction reaction during charging and discharging of the battery to at least one surface of the negative electrode current collectors 110 and 210, and then drying and rolling the same.
[0047] At this time, the negative electrode active layers 120 and 220 are divided into a central region, an edge region, and a sliding region in the width direction of the negative electrodes 100 and 200. Specifically, the negative electrode active layers 120 and 220 include central regions 121 and 221 that include a center portion in the width direction and have a ratio of 90% or more of the entire length based on the width direction. The central regions 121 and 221 are regions that constitute most of the negative electrode active layers 120 and 220, and may have a ratio of 93% or more, 95% or more, 97% or more, or 96% to 99% of the entire length in the width direction of the negative electrode active layers 120 and 220. Here, the "width direction of the negative electrode active layers 120 and 220" may mean a direction perpendicular to the direction in which the negative electrode current collector runs when the negative electrode is manufactured. In some cases, the "width direction of the negative electrode active layers 120 and 220" may be the same as the direction from one surface on which the negative electrode tab is formed to the opposite surface of the manufactured negative electrode. In the present invention, by adjusting the length ratios of the central regions 121 and 221 in the negative electrode active layers 120 and 220 to fall within the above range, the energy density of the negative electrode can be further increased.
[0048] Moreover, edge regions 122 and 222 are located outside the central regions 121 and 221 , and sliding regions 123 and 223 are located outside the edge regions 122 and 222 .
[0049] In this case, the edge region and the sliding region may be sequentially and continuously disposed on both sides of the central region 121 as shown in Fig. 1. In some cases, the edge region and the sliding region may be sequentially and continuously disposed only on one side of the central region 221 as shown in Fig. 2, when the electrode sheet is punched (or notched) during the manufacturing process of the negative electrode.
[0050] The sliding regions 123 and 223 are located at the edges of the negative electrode active layers 120 and 220 and have a thickness gradient. The sliding regions 123 and 223 may have a ratio of 3% or less of the entire length in the width direction of the negative electrode active layers 120 and 220. Specifically, the sliding regions 123 and 223 may have a shape in which the thickness decreases outward in the region adjacent to the edge regions 122 and 222, and may have a ratio of 2% or less, 1% or less, 0.5% or less, 0.01% to 1%, or 0.01% to 0.5% of the entire length in the width direction of the negative electrode active layers 120 and 220 in consideration of the energy density of the negative electrode. In this case, the above length ratio is the ratio of the overall length based on the width direction of the negative electrode active layers 120 and 220, and when sliding regions 123 and 223 are provided on both sides of the central region 121 as shown in FIG. 1, the length ratio of each sliding region may be reduced to half of the above length ratio.
[0051] Furthermore, the sliding regions 123 and 223 have a thickness gradient in which the thickness decreases toward the outside, so that the exposed surfaces can have a predetermined inclination angle with respect to the negative electrode current collectors 110 and 210. For example, the sliding regions 123 and 223 can have an inclination angle of 70° or more with respect to the negative electrode current collectors 110 and 210. Specifically, the sliding regions 123 and 223 can have an inclination angle of 75° or more, 80° or more, 85° or more, 70 to 85°, 75 to 80°, or 70 to 75° with respect to the negative electrode current collectors 110 and 210. In the present invention, by adjusting the inclination angle of the exposed surfaces of the sliding regions 123 and 223 relative to the negative electrode current collectors 110 and 210 within the above range, it is possible to prevent the N / P ratio from being reversed at the end of the electrode assembly assembled with the positive electrode, and to further improve the adhesive strength with the separator at the end of the negative electrode.
[0052] In addition, the edge regions 122 and 222 have a higher loading amount of negative electrode active material than the central regions 121 and 221, and therefore can suppress the N / P ratio from becoming smaller than 1 when the stacking position of the positive electrode active layer deviates from the negative electrode active layer inside the secondary battery, thereby preventing lithium from being precipitated at the ends of the negative electrode active layers 120 and 220.
[0053] At this time, the edge regions 122 and 222 may occupy the remaining length excluding the length ratio of the central regions 121 and 221 and the sliding regions 123 and 223. For example, the edge regions 122 and 222 may have a ratio of less than 7%, less than 5%, less than 4%, less than 2.5%, 0.09% to 3%, or 0.5 to 1% of the overall length in the width direction of the negative electrode active layers 120 and 220. When the edge regions 122 and 222 are provided on both sides of the central region 121, similarly to the sliding regions 123 and 223, the length ratio of each edge region may be reduced to half of the length ratio.
[0054] Furthermore, the anodes 100 and 200 according to the present invention have excellent characteristics in terms of fast charging performance. As described above, the anodes 100 and 200 can prevent lithium deposition at the ends of the anode active layers 120 and 220 due to the inversion of the N / P ratio between the anode and the cathode by controlling the loading amount per unit area of the carbon-based anode active material in the edge regions 122 and 222 to be higher than the loading amount per unit area of the carbon-based anode active material in the central regions 121 and 221. However, in this case, the edge regions 122 and 222, which have a high loading amount of the carbon-based anode active material, have a relatively increased structural tortuosity of the anode active layer compared to the remaining regions, which increases the migration distance of lithium ions and reduces the diffusion rate, so that lithium may be deposited on the anode surface during fast charging. In the anodes 100 and 200 of the present invention, the carbon-based anode active material contained in the anode active layers 120 and 220 is oriented so that the angle of the crystal plane of the carbon-based anode active material with respect to the surface of the anode current collectors 110 and 210 is low, and the oriented carbon-based anode active material in each region of the anode active layers 120 and 220 has a predetermined tendency, thereby solving such problems. Here, the orientation and / or alignment of the carbon-based anode active material (e.g., graphite) can be determined by a crystal plane analysis of the carbon-based anode active material (CA) contained in the anode active layer.
[0055] As an example, the negative electrode active layers 120 and 220 may satisfy the following formulas 1 and 2:
[0056] [Formula 1] 2.7≦[OI edge ] / [OI center ]≦4.8
[0057] [Formula 2] 1.5≦[OI sliding ] / [OI center ]≦2.6
[0058] (In formula 1 and formula 2, OI edge represents the alignment degree (OI) in the edge region, OI center represents the degree of alignment (OI) in the central region, OI sliding represents the degree of alignment (OI) in the sliding domain, The degree of alignment (OI) is the area (I 004 ) and the area of the peak representing the (1,1,0) crystal plane (I 110 ) percentage (I 004 / I 110 )
[0059] The degree of alignment (OI) of the carbon-based negative electrode active material (CA) can be an index showing the degree to which the crystal structure of the spherical carbon-based negative electrode active material is oriented in a certain direction, specifically, with respect to the surface of the negative electrode current collector, as measured by X-ray diffraction (XRD). More specifically, the negative electrode active layer shows peaks of 2θ=26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2° for the carbon-based negative electrode active material graphite as measured by X-ray diffraction, which indicate the (0,0,2) plane, (1,0,0) plane, (1,0,1)R plane, (1,0,1)H plane, (0,0,4) plane, and (1,1,0) plane. In addition, the peak appearing at 2θ=43.4±0.2° may be due to an overlap of the peaks corresponding to the (1,0,1)R plane of the carbon-based negative electrode active material (CA) and the (1,1,1) plane of the current collector, for example, copper (Cu).
[0060] Among these, the degree of alignment (OI) of the carbon-based negative electrode active material (CA) can be measured by the area ratio of the peak at 2θ=54.7±0.2° indicating the (0,0,4) plane and the peak at 2θ=77.5±0.2° indicating the (1,1,0) plane, specifically, the area ratio obtained by integrating the intensity of the above peaks. Here, the peak at 2θ=54.7±0.2° is a peak indicating the (0,0,4) plane, which has a tilt with respect to the negative electrode current collector, among the crystal planes of graphite. Therefore, the degree of alignment (OI) may mean that the closer the value is to 0, the closer the tilt to the surface of the negative electrode current collector is to 90°, and the larger the value is, the closer the tilt to the surface of the negative electrode current collector is to 0° or 180°. That is, in the negative electrode active layer according to the present invention, the carbon-based negative electrode active material (CA) is aligned at a high angle relative to the negative electrode current collector, for example, an angle of 60° or more, 70° or more, 70° to 90°, 80° to 90°, 65° to 85°, or 70° to 85° relative to the negative electrode current collector, so that the degree of alignment (OI) of the carbon-based negative electrode active material (CA) may be lower than when the carbon-based negative electrode active material (CA) is aligned at a lower angle.
[0061] Considering this, Equation 1 can be expressed as the degree of alignment (OI) of the carbon-based negative electrode active material contained in the central region. center The degree of alignment (OI) of the carbon-based negative active material contained in the edge region edge ) which means that the carbon-based negative electrode active material in the central region is aligned at a higher angle with respect to the negative electrode current collector surface than the carbon-based negative electrode active material in the edge regions. In the negative electrode active layers 120 and 220 of the present invention, the carbon-based negative electrode active material in the central region is aligned at a higher angle with respect to the negative electrode current collector surface than the carbon-based negative electrode active material in the edge regions, and the above formula 1 is satisfied within the range of 2.7 to 4.8 (i.e., 2.7≦[OI edge ] / [OI center ]≦4.8), specifically, 2.7 to 4.8 (i.e., 2.7≦[OI edge ] / [OI center ]≦4.8), 2.9~4.5 (i.e., 2.9≦[OI edge ] / [OI center ]≦4.5), 3.0~4.5 (i.e., 3.0≦[OI edge ] / [OIcenter ]≦4.5), 2.9~3.8 (i.e., 2.9≦[OI edge ] / [OI center ]≦3.8), 3.8~4.6 (i.e., 3.8≦[OI edge ] / [OI center ]≦4.6), or 3.1 to 4.2 (i.e., 3.1≦[OI edge ] / [OI center ]≦4.2).
[0062] In addition, Equation 2 represents the degree of alignment (OI center The degree of alignment (OI) of the carbon-based negative active material contained in the sliding region sliding ) which means that the carbon-based negative electrode active material in the central region is aligned at a higher angle with respect to the negative electrode current collector surface than the carbon-based negative electrode active material in the sliding region. In the negative electrode active layers 120 and 220 of the present invention, the carbon-based negative electrode active material in the central region is aligned at a higher angle with respect to the negative electrode current collector surface than the carbon-based negative electrode active material in the sliding region, and the above formula 2 is satisfied within the range of 1.5 to 2.6 (1.5≦[OI sliding ] / [OI center ]≦2.6), specifically, 1.8 to 2.6 (1.8≦[OI sliding ] / [OI center ]≦2.6), 1.7~2.3(1.7≦[OI sliding ] / [OI center ]≦2.3), 2.2~2.5(2.2≦[OI sliding ] / [OI center ]≦2.5), 1.9~2.2(1.9≦[OI sliding ] / [OI center ]≦2.2), or 2.0-2.5 (2.0≦[OI sliding ] / [OI center ]≦2.5).
[0063] In each region of the negative electrode active layers 120 and 220, the degree of alignment (OI) of the carbon-based negative electrode active material (CA) may satisfy a predetermined range so as to satisfy the conditions of the above formulas 1 and 2. As a result, the average degree of alignment of the carbon-based negative electrode active material (CA) contained in the entire negative electrode active layers 120 and 220 may be maintained low. Specifically, in the negative electrode active layers 120 and 220, the center regions 121 and 221 may have a low degree of alignment (OI) of the carbon-based negative electrode active material (CA) contained in the center regions. center The degree of alignment (OI) of the central regions 121 and 221 may be 0.7 to 1.5, more specifically, 0.7 to 1.3, 0.7 to 1.0, 0.9 to 1.2, or 0.8 to 1.1. center ) may have a deviation of 5% or less from the average alignment degree of the negative electrode active layers 120 and 220.
[0064] In addition, the degree of alignment (OI) of the carbon-based negative electrode active material contained in the edge regions 122 and 222 edge ) is the degree of alignment (OI) of the carbon-based negative electrode active material contained in the central regions 121 and 221. center This is because the loading amount of the carbon-based negative active material in the edge regions 122 and 222 is relatively large compared to the central regions 121 and 221. As a result, the carbon-based negative active material contained in the edge regions 122 and 222 becomes overcrowded during the rolling process after the orientation of the carbon-based negative active material, resulting in a decrease in the degree of alignment (OI). edge The degree of alignment (OI) of the carbon-based negative electrode active material is center ) may be somewhat higher.
[0065] The present invention can secure a shorter ion migration channel in each region by controlling the degree of alignment (OI) of the carbon-based anode active material (CA) contained in the center regions 121 and 221, the edge regions 122 and 222, and the sliding regions 123 and 223 of the anode active layers 120 and 220, respectively, as described above. As a result, the anode according to the present invention can prevent an increase in resistance due to a long migration distance of lithium ions during high-speed charging, thereby preventing a decrease in charging performance and preventing lithium deposition on the surface of the anode.
[0066] Meanwhile, the average thickness of the negative electrode active layers 120 and 220 may be 100 μm to 300 μm, specifically 100 μm to 250 μm, or 130 μm to 190 μm, and the average thickness may be the same as the average thickness of the central regions 121 and 221. By adjusting the average thickness of the negative electrode active layers 120 and 220 to fall within the above range, the present invention can easily control the orientation of the carbon-based negative electrode active material (CA) contained in each region, thereby improving the fast charging characteristics of the batteries including the negative electrodes 100 and 200.
[0067] In addition, the negative electrode active layers 120 and 220 may have a structure in which two individual layers are laminated depending on the battery model or product application to which the negative electrode of the present invention is applied, but are not limited thereto. In this case, the negative electrode according to the present invention may have a structure in which a first negative electrode active layer (not shown) is provided on the negative electrode current collectors 110 and 210, and a second negative electrode active layer (not shown) is provided on the first negative electrode active layer. In this case, the first negative electrode active layer and the second negative electrode active layer contain a carbon-based negative electrode active material (CA), and the carbon-based negative electrode active material (CA) contained in each layer may be the same or different.
[0068] In addition, the negative electrode active layers 120 and 220 include a carbon-based negative electrode active material (CA) as a negative electrode active material to realize electrical activity through a reversible oxidation-reduction reaction during charging and discharging of the battery.
[0069] The carbon-based negative active material (CA) refers to a material mainly composed of carbon atoms, and may include graphite. The graphite may include at least one of natural graphite and artificial graphite. Preferably, the CA may include natural graphite or a mixture of natural graphite and artificial graphite.
[0070] The carbon-based negative electrode active material (CA) is preferably a spherical graphite granule formed by the aggregation of a plurality of flake graphite. Examples of flake graphite include natural graphite, artificial graphite, mesophase calcined carbon (bulk mesophase) made from tar and pitch, graphitized cokes (raw coke, green coke, pitch coke, needle coke, petroleum coke, etc.), etc. In particular, a graphite granule assembled from a plurality of natural graphites having high crystallinity is preferable. In addition, one graphite granule may be formed by the aggregation of 2 to 100 flake graphite particles, preferably 3 to 20 flake graphite particles.
[0071] In addition, the carbon-based negative electrode active material (CA) has an average particle size (D 50 Specifically, the average particle size (D) can be 0.5 μm to 15 μm, 0.5 μm to 10 μm, 5 μm to 20 μm, 10 μm to 20 μm, 12 μm to 18 μm, 2 μm to 7 μm, 0.5 μm to 5 μm, or 1 μm to 3 μm. 50 ) can be shown.
[0072] The average particle size of natural graphite may be advantageously small to maximize the degree of disorder in the expansion direction of each particle so as to prevent the particles from expanding due to charging with lithium ions. However, when the particle size of natural graphite is less than 0.5 μm, a large amount of binder may be required due to an increase in the number of particles per unit volume. On the other hand, when the maximum particle size exceeds 20 μm, the expansion becomes intense and the adhesion between particles and between the particles and the current collector decreases due to repeated charging and discharging, and the cycle characteristics may be significantly reduced.
[0073] In addition, the negative electrode active layer according to the present invention may further selectively contain a conductive material, a binder, other additives, and the like, as necessary, in addition to the carbon-based negative electrode active material (CA) that is the main component.
[0074] The conductive material may include, but is not limited to, one or more of carbon black, acetylene black, ketjen black, carbon nanotubes, carbon fibers, and the like.
[0075] For example, the negative electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., alone or in combination, as a conductive material.
[0076] At this time, the content of the conductive material may be 0.1 parts by weight to 10 parts by weight based on 100 parts by weight of the total negative electrode active layer. Specifically, the content of the conductive material may be 0.1 parts by weight to 8 parts by weight, 0.1 parts by weight to 5 parts by weight, 0.1 parts by weight to 3 parts by weight, 2 parts by weight to 6 parts by weight, or 0.5 parts by weight to 2 parts by weight. By controlling the content of the conductive material within the above range, the present invention can prevent the increase in the resistance of the negative electrode due to a low content of the conductive material, resulting in a decrease in the charging capacity. In addition, the present invention can prevent problems such as a decrease in the content of the negative electrode active material due to an excessive amount of the conductive material, resulting in a decrease in the charging capacity, or a decrease in the rapid charging characteristics due to an increase in the loading amount of the negative electrode active layer.
[0077] In addition, the binder is a component that aids in bonding between the negative electrode active material and the conductive material and the current collector, and may be suitably applied within a range that does not deteriorate the electrical properties of the electrode. Specifically, the binder may include any one or more of vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene butadiene rubber (SBR), and fluororubber.
[0078] The content of the binder may be 0.1 to 10 parts by weight, specifically 0.1 to 8 parts by weight, 0.1 to 5 parts by weight, 0.1 to 3 parts by weight, or 2 to 6 parts by weight, based on 100 parts by weight of the total negative electrode active layer. By controlling the content of the binder contained in the negative electrode active layer within the above range, the present invention can prevent a decrease in adhesive strength of the active layer due to a low content of the binder, or a decrease in electrical properties of the electrode due to an excessive amount of the binder.
[0079] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, nickel, titanium, calcined carbon, etc., and in the case of copper or stainless steel, it may be surface-treated with carbon, nickel, titanium, silver, etc. The average thickness of the negative electrode current collector may be suitably 1 μm to 500 μm, taking into consideration the conductivity and total thickness of the negative electrode to be manufactured.
[0080] <Lithium secondary battery>
[0081] In one embodiment, the present invention further comprises: There is provided a lithium secondary battery comprising an electrode assembly including a positive electrode, the above-described negative electrode of the present invention, and a separator disposed between the positive electrode and the negative electrode.
[0082] The lithium secondary battery according to the present invention includes an electrode assembly in which a plurality of positive electrodes, a separator, and a negative electrode are sequentially arranged, and an electrolyte composition in which a lithium salt and an electrolyte additive are dissolved in a non-aqueous organic solvent. The lithium secondary battery includes a structure in which a negative electrode active layer is laminated on a negative electrode current collector, the negative electrode active layer is divided into a center region, an edge region, and a sliding region, and includes a negative electrode in which the degree of alignment (OI) of each carbon-based negative electrode active material contained in the center region, the edge region, and the sliding region satisfies Equation 1 and Equation 2. As a result, the lithium secondary battery has an advantage in that lithium deposition does not occur at the edge of the negative electrode active layer during charging and discharging, and the lithium secondary battery has excellent high-speed charging characteristics.
[0083] In this case, the negative electrode has the same configuration as that described above, and therefore a detailed description thereof will be omitted.
[0084] The positive electrode may include a positive electrode active layer prepared by applying a slurry containing a positive electrode active material onto a positive electrode current collector, drying and rolling the slurry, and the positive electrode active layer may further include a conductive material, a binder, and other additives, if necessary, in addition to the positive electrode active material.
[0085] The positive electrode active material is a material capable of electrochemically reacting on a positive electrode current collector, and may include at least one of lithium metal oxides represented by the following Chemical Formula 1 and Chemical Formula 2 capable of reversibly intercalating and deintercalating lithium ions:
[0086] [Chemical formula 1] Li x [Ni y Co z Mn w M 1 v ]O2
[0087] [Chemical formula 2] LiM 2 p Mn q P r O4
[0088] In the above Chemical Formula 1 and Chemical Formula 2, M 1 is one or more of the elements W, Cu, Fe, V, Cr, Ti, Zr, Zn, Al, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ca, Ce, Nb, Mg, B, and Mo; x, y, z, w, and v are 1.0≦x≦1.30, 0.5≦y<1, 0 <z≦0.3、0<w≦0.3、0≦v≦0.1であり、かつ、y+z+w+v=1であり、 M 2 is Ni, Co or Fe, p is 0.05≦p≦1.0, q is 1-p or 2-p; r is 0 or 1.
[0089] The lithium metal oxides represented by Chemical Formula 1 and Chemical Formula 2 above are materials containing high amounts of nickel (Ni) and manganese (Mn), respectively, and when used as a positive electrode active material, have the advantage of being able to stably supply high capacity and / or high voltage electricity compared to conventionally commonly used positive electrode active materials such as iron phosphate oxide (LiFeO4).
[0090] In this case, the lithium metal oxide represented by the above chemical formula 1 is LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.6 Co 0.2 Mn 0.1 Al 0.1 O2, LiNi 0.6Co 0.2 Mn 0.15 Al 0.05 O2, LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2, etc., and the lithium metal oxide represented by the above chemical formula 2 is LiNi 0.7 Mn 1.3 O4, LiNi 0.5 Mn 1.5 O 4、 LiNi 0.3 Mn 1.7 O4, LiFePO4, LiFe 0.7 Mn 0.3 PO4, etc., which may be used alone or in combination.
[0091] The positive electrode active material may be included in an amount of 85 parts by weight or more, specifically 90 parts by weight or more, 93 parts by weight or more, or 95 parts by weight or more, based on the weight of the positive electrode active layer.
[0092] The positive electrode active layer may further include a conductive material, a binder, and other additives in addition to the positive electrode active material.
[0093] At this time, the conductive material is used to improve the electrical performance of the positive electrode, and may be a conductive material commonly used in the art. Specifically, the conductive material may include one or more of natural graphite, artificial graphite, carbon black, acetylene black, denka black, ketjen black, super P, channel black, furnace black, lamp black, thermal black, graphene, and carbon nanotubes.
[0094] The conductive material may be included in an amount of 0.1 to 5 parts by weight based on the weight of each positive electrode active layer, specifically 0.1 to 4 parts by weight, 2 to 4 parts by weight, 1.5 to 5 parts by weight, 1 to 3 parts by weight, 0.1 to 2 parts by weight, or 0.1 to 1 part by weight.
[0095] In addition, the binder plays a role of binding the positive electrode active material, the positive electrode additive, and the conductive material to each other, and may be used without any particular limitation as long as it has such a function. Specifically, the binder may include one or more resins selected from polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVDF), polyacrylonitrile, polymethylmethacrylate, and copolymers thereof. As an example, the binder may include polyvinylidene fluoride.
[0096] The binder may be included in an amount of 1 to 10 parts by weight, specifically 2 to 8 parts by weight, or 1 to 5 parts by weight, based on the weight of each positive electrode active layer.
[0097] The total thickness of the positive electrode active layer is not particularly limited, but may be specifically 50 μm to 300 μm, more specifically 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm, or 150 μm to 190 μm.
[0098] In addition, the positive electrode may use a positive electrode current collector having high conductivity without inducing chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, calcined carbon, etc. may be used, and in the case of aluminum or stainless steel, those surface-treated with carbon, nickel, titanium, silver, etc. may also be used. In addition, the average thickness of the current collector may be suitably applied to be 3 μm to 500 μm, taking into consideration the conductivity and total thickness of the positive electrode to be manufactured.
[0099] Meanwhile, the separator interposed between the positive and negative electrodes of each unit cell is an insulating thin film having high ion permeability and mechanical strength, and is not particularly limited as long as it is one commonly used in the art, specifically, one containing at least one polymer selected from polypropylene, polyethylene, and polyethylene-propylene copolymers having chemical resistance and hydrophobicity may be used. The separator may have a porous polymer substrate such as a sheet or nonwoven fabric containing the above-mentioned polymer, and may have a composite separator formed by coating organic or inorganic particles on the porous polymer substrate with an organic binder. The separator may have an average pore diameter of 0.01 μm to 10 μm and an average thickness of 5 μm to 300 μm.
[0100] Meanwhile, the lithium secondary battery according to the present invention is not particularly limited, but may be a secondary battery having a form including a stack type, a zigzag type, or a zigzag-stack type electrode assembly. As one example, the lithium secondary battery according to the present invention may be a pouch type secondary battery or a prismatic type secondary battery.
[0101] <Method of manufacturing the negative electrode>
[0102] In one embodiment, the present invention further comprises: Applying a negative electrode slurry containing a carbon-based negative electrode active material onto a negative electrode current collector; applying a magnetic field to the applied negative electrode slurry; and drying the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer; The negative electrode active layer is divided into a central region including a center portion in a width direction of the negative electrode active layer, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region, and the negative electrode active layer satisfies the following formulas 1 and 2:
[0103] [Formula 1] 2.7≦[OI edge ] / [OI center ]≦4.8
[0104] [Formula 2] 1.5≦[OI sliding ] / [OI center ]≦2.6
[0105] (In formula 1 and formula 2, OI edge represents the alignment degree (OI) in the edge region, OI center represents the degree of alignment (OI) in the central region, OI sliding represents the degree of alignment (OI) in the sliding domain, The degree of alignment (OI) is the area (I 004 ) and the area of the peak representing the (1,1,0) crystal plane (I 110 ) percentage (I 004 / I 110 )
[0106] The method for manufacturing a negative electrode according to the present invention may include coating a negative electrode slurry including a carbon-based negative electrode active material on a negative electrode current collector, applying a magnetic field to a surface of the coated negative electrode slurry, thereby aligning the carbon-based negative electrode active material in the negative electrode slurry at a predetermined angle with respect to the surface of the negative electrode current collector, and then drying the negative electrode slurry in which the degree of alignment of the carbon-based negative electrode active material is reduced to form a negative electrode active layer, thereby manufacturing a negative electrode.
[0107] Here, the step of applying the negative electrode slurry is a step of discharging and coating the negative electrode slurry containing a carbon-based negative electrode active material onto the surface of a moving negative electrode current collector, and may be applied without any particular limitation as long as it is a method commonly used in the art. Preferably, the step of applying the negative electrode slurry may be performed using a die coating method. The die coating method may be performed using a slot die having a shim for controlling the discharging condition of the negative electrode slurry. In this case, the loading amount and coating thickness of the negative electrode slurry applied onto the negative electrode current collector may be easily controlled by controlling the shape of the shim.
[0108] In addition, the step of applying the negative electrode slurry may apply the negative electrode slurry so as to satisfy the following formula 3 in order to prevent lithium from being deposited at the end of the negative electrode active layer during charging and discharging of the secondary battery:
[0109] [Formula 3] R sliding <R center <R edge
[0110] (In formula 3, R sliding represents the average thickness of the anode slurry in the sliding region, R edge represents the average thickness of the anode slurry at the edge region, R center represents the average thickness of the anode slurry in the central region)
[0111] Equation 3 shows the correlation between the average thickness of the negative electrode slurry applied to each region, and the negative electrode slurry applied according to the present invention may have a tendency to be formed such that the average thickness in the edge region 122 is greater than the average thickness in the center region 121, and the average thickness in the sliding region 123 is significantly reduced according to the thickness gradient, as shown in FIG. 3. Here, the "average thickness" may be measured using a confocal microscope, and the method may vary depending on each region. Specifically, in the case of the center region and the edge region, the average thickness may be measured at three or more arbitrary points and calculated from the measured values. In the case of the sliding region, the thickness may be measured at a point where the length of the sliding region is 1 / 2 based on the width direction length of the applied negative electrode slurry.
[0112] For example, the anode slurry center regions 121 and 221 may have an average thickness of 180±3 μm, edge regions 122 and 222 may have an average thickness of 210±3 μm, and sliding regions 123 and 223 may have an average thickness of 120±3 μm.
[0113] By controlling the average thickness of each region of the negative electrode slurry applied on the negative electrode current collector as described above, the present invention can easily control the loading amount of the carbon-based negative electrode active material in each region even if the average thickness of each region after rolling is uniform. Specifically, even if the average thicknesses of the central regions 121 and 221 and the edge regions 122 and 222 of the negative electrode active layer are the same or similar after rolling, the loading amount per unit area of the edge regions 122 and 222 may be greater than the loading amount per unit area of the central regions 121 and 221.
[0114] Meanwhile, the step of applying a magnetic field to the negative electrode slurry may be a step of orienting a crystal plane of the carbon-based negative electrode active material contained in the negative electrode slurry to have a predetermined angle with respect to the negative electrode current collector. To this end, the step of applying a magnetic field may be performed by magnet units disposed on the upper and lower parts of the negative electrode current collector, which is moved after the negative electrode slurry is applied to its surface.
[0115] Here, the degree of alignment (OI) of the carbon-based negative active material contained in the negative electrode slurry can be adjusted by the strength of the applied magnetic field, the time of exposure to the magnetic field, etc. Thus, the step of applying the magnetic field can be performed under predetermined magnetic field strength and time conditions.
[0116] Specifically, the step of applying the magnetic field may apply a magnetic field of 2,000 G (Gauss) to 6,000 G (Gauss). Specifically, the step of applying the magnetic field may apply a magnetic field with an intensity of 2,500 G to 5,500 G, 3,000 G to 5,500 G, 3,500 G to 5,500 G, 4,000 G to 5,500 G, 3,500 G to 4,500 G, or 4,500 G to 5,000 G.
[0117] Furthermore, the step of applying the magnetic field may be performed for 5 to 60 seconds, specifically for 10 to 60 seconds, 10 to 30 seconds, 30 to 60 seconds, 40 to 50 seconds, 15 to 35 seconds, or 10 to 50 seconds.
[0118] As one example, in the step of applying a magnetic field, a magnetic field of 4,700±100 G may be applied to the negative electrode slurry for 12 to 33 seconds.
[0119] Furthermore, the step of applying the magnetic field is performed by magnet parts introduced to the upper and lower parts of the applied negative electrode slurry as described above, and the size of the magnet parts can be adjusted to be larger than the size of the negative electrode slurry so that the magnetic field applied to the negative electrode slurry can be uniformly applied to the entire surface of the negative electrode slurry. For example, the magnet parts may have a length ratio of 105% to 200% based on the width direction length of the negative electrode slurry, and specifically, may have a length ratio of 110% to 180%, 110% to 160%, 110% to 140%, 110% to 130%, 130% to 150%, or 105% to 120% based on the width direction length of the negative electrode slurry.
[0120] In the present invention, by controlling the strength of the magnetic field, the application time, and / or the size of the magnet part as described above in the step of applying the magnetic field, the regional orientation of the carbon-based negative electrode active material contained in the negative electrode slurry can be controlled to satisfy Equation 1 and Equation 2.
[0121] In addition, the step of forming the negative electrode active layer may include the steps of drying the negative electrode slurry and rolling the dried negative electrode slurry.
[0122] At this time, the step of drying the negative electrode slurry may be performed in any manner that can maintain the orientation of the carbon-based negative electrode active material contained in the negative electrode active layer.
[0123] For example, the drying step may dry the negative electrode slurry by applying thermal energy to the negative electrode slurry using a hot air dryer, a vacuum oven, or the like.
[0124] The step of rolling the dried negative electrode slurry is a step of increasing the density of the negative electrode active layer by applying pressure to the dried negative electrode slurry using a roll press, etc. Here, the rolling may be performed at a temperature condition higher than room temperature.
[0125] Specifically, the rolling can be carried out at a temperature of 50°C to 100°C, more specifically, at a temperature of 60°C to 100°C, 75°C to 100°C, 85°C to 100°C, 50°C to 90°C, 60°C to 80°C, or 65°C to 90°C. Specifically, the rolling may be performed at a rolling speed of 2 m / s to 7 m / s, more specifically, at a rolling speed of 2 m / s to 6.5 m / s, 2 m / s to 6 m / s, 2 m / s to 5.5 m / s, 2 m / s to 5 m / s, 2 m / s to 4.5 m / s, 2 m / s to 4 m / s, 2.5 m / s to 4 m / s, 2.5 m / s to 3.5 m / s, 3.5 m / s to 5 m / s, 5 m / s to 7 m / s, 5.5 m / s to 6.5 m / s, or 6 m / s to 7 m / s. The rolling may be carried out under a pressure condition of 50 MPa to 200 MPa, specifically, under a pressure condition of 50 MPa to 150 MPa, 50 MPa to 100 MPa, 100 MPa to 200 MPa, 150 MPa to 200 MPa, or 80 MPa to 140 MPa.
[0126] The present invention can increase the energy density of the negative electrode while minimizing the change in the degree of alignment of the carbon-based negative electrode active material contained in the negative electrode active layer formed by rolling the dried negative electrode slurry under the above-mentioned temperature, speed and / or pressure conditions.
[0127] The present invention will now be described in more detail with reference to examples and experimental examples.
[0128] However, the following examples and experimental examples are merely illustrative of the present invention, and the content of the present invention is not limited to the following examples and experimental examples.
[0129] <Examples 1-2 and Comparative Examples 1-2. Production of negative electrodes for lithium secondary batteries>
[0130] A negative electrode for a lithium secondary battery was manufactured according to the conditions shown in Table 1 below.
[0131] First, natural graphite (average particle size: 10±1 μm) and artificial graphite (average particle size: 8±1 μm) were prepared as carbon-based negative electrode active materials, and negative electrode slurries were produced using the prepared carbon-based negative electrode active materials.
[0132] Specifically, a graphite mixture of natural graphite and artificial graphite in a weight ratio of 1-3:7-9 was prepared as the negative electrode active material, carbon black was prepared as the conductive material, and carboxymethylcellulose (CMC) and styrene-butadiene rubber (SBR) were prepared as the binder. Then, 95 parts by weight of the graphite mixture, 1 part by weight of carbon black, 1.5 parts by weight of carboxymethylcellulose (CMC), and 2.5 parts by weight of styrene-butadiene rubber (SBR) were mixed with water to a solid content of 50% to produce a negative electrode slurry.
[0133] After the negative electrode slurry was prepared, it was cast onto a copper sheet (thickness: 10 μm) that was being transported roll-to-roll (transport speed: 5 m / min) using a die coater. At this time, the negative electrode slurry was cast to an average thickness of 190 μm along the transport direction of the copper sheet, and the shape of the shim installed in the die coater was changed so that the average thickness of each region of the negative electrode active layer before rolling was adjusted as shown in Table 1.
[0134] At this time, the cross-sectional structure of the applied negative electrode slurry was as shown in Figure 3, and each negative electrode slurry had a central region with a length ratio of 98.5% based on the width direction length of the negative electrode slurry. Then, regions arranged on both sides of the central region with a total length ratio of 1.0% were set as edge regions (length ratio of 0.5% each), and regions arranged on the outside of the edge regions with a length ratio of 0.5% were set as sliding regions (length ratio of 0.25% each).
[0135] In measuring the average thickness of each set region, the confocal thickness of the center region and edge region of the negative electrode slurry was measured three times for each region, and the average thickness was calculated by calculating the average thickness. The average thickness of the sliding region of the negative electrode slurry was defined as the thickness at the point where the length of the sliding region was 1 / 2 based on the width direction length of the negative electrode slurry.
[0136] Once the average thickness of each region of the negative electrode slurry was measured, permanent magnets with a length ratio of 110~120% of the width direction length of the negative electrode slurry were placed on top of the applied negative electrode slurry and under the negative electrode current collector, and a magnetic field of 4,700±100G was applied for 15 seconds, after which the negative electrode slurry to which the magnetic field was applied was dried with hot air to form a negative electrode active layer. The formed negative electrode active layer was rolled at 50±1°C, a pressure of 100~150MPa and a transfer speed of 3m / s to manufacture a negative electrode for a lithium secondary battery.
[0137] In addition, X-ray diffraction spectroscopy (XRD) was performed on each region of the negative electrode active layer of each manufactured negative electrode to measure the spectrum. At this time, the measurement conditions of X-ray diffraction (XRD) were as follows:
[0138] - Target: Cu (Kα line) graphite monochromator -Slit: Divergence slit = 1 degree, Receiving slit = 0.1mm, Scattering slit = 1 degree -Measurement area: (1,1,0) plane: 76.5 degrees < 2θ < 78.5 degrees / (0,0,4) plane: 53.5 degrees < 2θ < 56.0 degrees
[0139] From the spectrum measured under the above conditions, the areas of the peaks representing the (0,0,4) crystal plane and the (1,1,0) crystal plane were calculated, and the ratio of these areas (I 004 / I 110 The degree of alignment (OI) of the mixed graphite in each region was calculated by calculating the degree of alignment (OI) of the mixed graphite in each region. The calculated values are shown in Table 1 below.
[0140] [Table 1]
[0141] <Comparative Examples 3 and 4. Production of negative electrodes for lithium secondary batteries>
[0142] A negative electrode for a lithium secondary battery was manufactured in the same manner as in Example 1, except that a magnetic field was not applied after casting of the negative electrode slurry, or a magnetic field was applied using a permanent magnet having a length ratio of 95 to 100% based on the width direction length of the negative electrode slurry.
[0143] During the preparation of the negative electrode, (1) the average thickness of each region of the applied negative electrode slurry and (2) the degree of alignment (OI) of the carbon-based negative electrode active material contained in each region after rolling were measured in the same manner as in Example 1, and the measurement results are shown in Table 2 below.
[0144] [Table 2]
[0145] <Examples 3 to 4 and Comparative Examples 5 to 8. Production of Lithium Secondary Batteries>
[0146] The positive electrode active material is LiNi with a particle size of 5 μm. 0.7 Co 0.1 Mn 0.1 Al 0.1 O2 was prepared and mixed with polyvinylidene fluoride as a carbon-based conductive material and binder in N-methylpyrrolidone (NMP) in a weight ratio of 94:3:3 to form a slurry, which was then cast onto an aluminum sheet, dried in a vacuum oven at 120°C, and rolled to produce a positive electrode.
[0147] The positive electrode obtained above and the negative electrode prepared in each of Examples 1-2 and Comparative Examples 1-4 were inserted into a case with a separator made of polypropylene having a thickness of 18 μm therebetween, and then an electrolyte composition was injected to assemble a lithium secondary battery.
[0148] The type of negative electrode applied to each lithium secondary battery is shown in Table 3 below.
[0149] [Table 3]
[0150] <Experimental Example>
[0151] In order to evaluate the performance of the negative electrode according to the present invention, the following experiment was carried out.
[0152] a) Evaluation of the presence or absence of lithium deposition
[0153] The lithium secondary batteries manufactured in Examples 3-4 and Comparative Examples 5-8 were charged to 80% SOC by applying a current of 1.5C-rate, and the voltage change and dV / dQ according to the SOC were measured. If a voltage plateau was present in the measured voltage change, or if the graph showing dV / dQ was bimodal, it was determined that lithium had been deposited on the negative electrode surface. The results are shown in Table 4 below.
[0154] B) Evaluation of quick charging performance The lithium secondary batteries manufactured in Examples 3 and 4 and Comparative Examples 5 to 8 were subjected to a charge / discharge cycle of discharging at 0.5 C and then charging at a charging rate of 1.7 C 300 times, and then the charge capacity and charge rate were measured. The measured charge capacity and its ratio to the initial charge capacity were calculated, and the results are shown in Table 4 below. When the ratio to the calculated initial charge capacity was 80% or more, it was marked with "◯", when it was 50% or less, it was marked with "X", and when it was more than 50% but less than 80%, it was marked with "△".
[0155] [Table 4]
[0156] As shown in Table 4, the negative electrode for a lithium secondary battery according to the present invention not only suppresses lithium deposition, but also has excellent rapid charging performance. Specifically, it was confirmed that the negative electrode produced in the examples does not deposit lithium on the surface of the negative electrode during charging and discharging, and maintains 80% or more of the charge capacity during rapid charging.
[0157] This means that the negative electrode of the embodiment contains a high loading amount of carbon-based negative electrode active material in the edge region of the negative electrode active layer, which is effective in suppressing lithium deposition during charging of the battery, and the degree of alignment (OI) of each carbon-based negative electrode active material contained in the central region, edge region, and sliding region of the negative electrode active layer satisfies Equation 1 and Equation 2, thereby improving the fast charging performance of the battery.
[0158] From these results, it is understood that the negative electrode for a lithium secondary battery according to the present invention suppresses lithium deposition at the ends of the negative electrode active layer, and a secondary battery including the same has excellent rapid charging performance.
[0159] Although the present invention has been described above with reference to preferred embodiments, a person skilled in the art or having ordinary knowledge in the art will understand that the present invention can be modified and changed in various ways without departing from the spirit and technical scope of the present invention as described in the claims below.
[0160] Therefore, the technical scope of the present invention is not limited to the contents described in the Summary of the Invention of the specification, but is defined by the claims. [Explanation of symbols]
[0161] 100, 200: Negative electrode for lithium secondary battery according to the present invention 110, 210: Negative electrode current collector 120, 220: Negative electrode active layer 121, 221: central region of negative electrode active layer 122, 222: edge region of negative electrode active layer 123, 223: Sliding area of negative electrode active layer CA: Carbon-based negative electrode active material ↑: Crystal plane alignment direction of carbon-based negative electrode active material
Claims
1. a negative electrode current collector; and a negative electrode active layer provided on at least one surface of the negative electrode current collector and containing a carbon-based negative electrode active material, The negative electrode active layer is The negative electrode active layer is divided into a central region including a center portion in a width direction of the negative electrode active layer, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region, A negative electrode for a lithium secondary battery that satisfies the following formulas 1 and 2: [Formula 1] 2.7≦[O.I] edge ] / [O.I center ]≦4.8 [Formula 2] 1.5≦[O.I] sliding ] / [O.I center ]≦2.6 In Formula 1 and Formula 2, O.I. edge represents the alignment degree (O.I) in the edge region, O.I. center represents the degree of alignment (O.I) in the central region, O.I. sliding represents the degree of alignment (O.I) in the sliding region, The degree of alignment (O.I) is the area (I 004 ) and the area of the peak representing the (1,1,0) crystal plane (I 110 ) ratio (I 004 / I 110 )
2. The central region of the negative electrode active layer has an alignment degree (O.I. center 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the ratio of ZnO to MnO is 0.7 to 1.
5.
3. the central region of the negative electrode active layer has a ratio of 90% or more of the entire length in the width direction of the negative electrode active layer, 3. The negative electrode for a lithium secondary battery according to claim 1, wherein the sliding region of the negative electrode active layer has a ratio of 3% or less of the entire length in a width direction of the negative electrode active layer.
4. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the central region of the negative electrode active layer has an average thickness of 100 μm to 300 μm.
5. The negative electrode for a lithium secondary battery according to claim 1 , wherein the carbon-based negative electrode active material comprises at least one of natural graphite and artificial graphite.
6. Applying a negative electrode slurry containing a carbon-based active material onto a negative electrode current collector; applying a magnetic field to the applied negative electrode slurry; and drying the negative electrode slurry to which the magnetic field is applied to form a negative electrode active layer; The negative electrode active layer is divided into a central region including a center portion in a width direction of the negative electrode active layer, a sliding region located at an edge of the negative electrode active layer and having a thickness gradient, and an edge region located between the central region and the sliding region, and satisfies the following formulas 1 and 2: [Formula 1] 2.7≦[O.I] edge ] / [O.I center ]≦4.8 [Formula 2] 1.5≦[O.I] sliding ] / [O.I center ]≦2.6 In Formula 1 and Formula 2, O.I. edge represents the alignment degree (O.I) in the edge region, O.I. center represents the degree of alignment (O.I) in the central region, O.I. sliding represents the degree of alignment (O.I) in the sliding region, The degree of alignment (O.I) is the area (I 004 ) and the area of the peak representing the (1,1,0) crystal plane (I 110 ) ratio (I 004 / I 110 )
7. 7. The method for producing a negative electrode for a lithium secondary battery according to claim 6, wherein in the step of applying the negative electrode slurry, the applied negative electrode slurry satisfies the following formula 3: [Formula 3] R sliding <R center <R edge In formula 3, R sliding represents the average thickness of the sliding region, R edge represents the average thickness of the edge region, R center represents the average thickness of the central region.
8. 7. The method for producing a negative electrode for a lithium secondary battery according to claim 6, wherein the step of applying a magnetic field applies a magnetic field of 2,000 G to 6,000 G.
9. The method for producing a negative electrode for a lithium secondary battery according to claim 6, wherein the step of applying the magnetic field is performed for 5 seconds to 60 seconds.
10. 7. The method for manufacturing a negative electrode for a lithium secondary battery according to claim 6, wherein the step of applying the magnetic field is performed by magnet parts introduced to the upper and lower parts of the applied negative electrode slurry, and the magnet parts have a length of 105% to 200% based on the width direction length of the negative electrode slurry.
11. The step of forming the negative electrode active layer includes: drying the negative electrode slurry; and rolling the dried negative electrode slurry.
Citation Information
Patent Citations
Negative electrode slurry and preparation method thereof, negative plate and preparation method thereof, lithium ion battery and application thereof
CN110931734A
Nonaqueous electrolyte secondary battery
JP2014086258A
Negative electrode for secondary battery
JP2018129212A
Anode for lithium ion secondary battery, method for preparing the same, and lithium ion secondary battery comprising the same
JP2022074139A
Negative electrode for lithium secondary battery and lithium secondary battery including the same
JP2022167890A